Modelos matemáticos para o problema integrado de dimensionamento de lotes e corte de estoque unidimensional - Longhi, Aneliza Leandro [UNESP]; Melega, Gislaine Mara [UNESP]; Araujo, Silvio Alexandre de [UNESP] (My University, 2015)
The lot-sizing and the one-dimensional cutting-stock problems play an important role in several production sectors, such as, tubular furniture factories, paper plants, and metallurgical industries. These problems are generally dealt independently. In this work, we approached both problems in an integrated way. We considered a classical model for lot sizing problem and its reformulation based on the shortest path problem. Concerning the one-dimensional cutting stock problem, we extend three different models from literature considering multiple periods. Based on the models studied, we proposed formulations that treat the problems in an integrated way. A computational study was performed using randomly generated data. The aim of this study was to assess the quality of integrated models in different aspects.

Os problemas de dimensionamento de lotes e corte de estoque unidimensional são importantes em diversos setores industriais, tais como, fábricas de móveis tubulares e de papel, metalúrgicas, entre outros e, geralmente, estes problemas são tratados de maneira independente. Neste trabalho, abordamos os dois problemas de maneira integrada. Consideramos um modelo clássico para o problema de dimensionamento de lotes, bem como sua reformulação baseada no problema de caminho mínimo. Para o problema de corte de estoque unidimensional, foram estendidos três diferentes modelos encontrados na literatura de forma a considerar vários períodos de tempo. A partir destes modelos, foram propostas formulações que tratam os problemas de maneira integrada. Um estudo computacional foi realizado utilizando dados gerados aleatoriamente, com o objetivo de avaliar a qualidade dos modelos integrados em diferentes aspectos.
Keywords: Lot-sizing problems; One-dimensional cutting stock problems; Integrated problems; Problemas de dimensionamento de lotes; Problemas de corte de estoque unidimensional; Problemas integrados